Neurogenic orthostatic hypotension in early stage Parkinson's disease: New insights from the first 105 patients of the BoProPark study. (December 2021) - Baschieri, Francesca; Sambati, Luisa; Guaraldi, Pietro; Barletta, Giorgio; Cortelli, Pietro; Calandra-Buonaura, Giovanna
Abstract: Objectives: The prevalence of neurogenic orthostatic hypotension (NOH, due to cardiovascular autonomic failure) at early stage of Parkinson's disease (PD) is unknown. The aims of this study are to prospectively evaluate in a cohort of PD patients recruited within 3 years from motor onset (1) cardiovascular autonomic functions by means of cardiovascular reflex tests (CRTs) and the occurrence of NOH; (2) the frequency of orthostatic symptoms with a validated questionnaire. Methods: We included the first 105 PD patients of the prospective "BoProPark" study. Each patient underwent CRTs (head up tilt test; Valsalva manoeuvre; deep breathing; cold face test and handgrip test) under continuous blood pressure monitoring according to standardized procedures and SCOPA-Aut questionnaire at baseline (T0) and after 16 months (T1). A group of 50 age- and sex-matched controls was used for comparison. Results: At T0 (mean age 61 ± 9 years, disease duration 19 ± 9 months) NOH was detected in 4/105 (3.8%) patients, whereas at T1 in 8/105 (7.6%). CRTs responses assessing sympathetic function were impaired at T0 in PD patients compared to controls and progressively worsened at T1. Only 1 patient at T0 and 3 at T1 with NOH reported orthostatic symptoms with low frequency, while the majority of patients reporting these symptoms did not have OH at testing. Conclusions: Our prospective study shows that NOH is not common at early PD stage. Asymptomatic mild sympathetic impairment was observed at first evaluation and progressed with disease evolution. Secondary OH may account for the higher prevalence of OH in PD reported so far. Highlights: Neurogenic orthostatic hypotension is rare in our cohort of early Parkinson's disease. Orthostatic hypotension in early Parkinson's disease is mainly asymptomatic. Early Parkinson's disease presents mild adrenergic impairment progressing over time.